2020
DOI: 10.3390/nano10101955
|View full text |Cite
|
Sign up to set email alerts
|

Mycosynthesis of Silver Nanoparticles Using Screened Trichoderma Isolates and Their Antifungal Activity against Sclerotinia sclerotiorum

Abstract: To control the disease caused by Sclerotinia sclerotiorum, a total of 15 isolates of the Trichoderma species was screened for the biosynthesis of silver nanoparticles (AgNPs). Among them, the highest yield occurred in the synthesis of AgNPs using a cell-free aqueous filtrate of T.virens HZA14 producing gliotoxin. The synthetic AgNPs were charactered by SEM, EDS, TEM, XRD, and FTIR. Electron microscopy studies revealed that the size of AgNPs ranged from 5–50 nm and had spherical and oval shapes with smooth surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…The results corroborated those of Ahluwalia et al [21], who reported that silver nanoparticles biosynthesized by T. harzianum exhibited spherical AgNPs with a range of diameters within the standard error of the mean. According to Tomah et al [36], SEM micrographs revealed that the exterior surfaces of AgNPs generated from cell-free T. virens HZA14 filtrate were spherical with a size range of 5 to 50 nm. Hirpara et al [24] demonstrated that silver nanoparticles biosynthesized by T. interfusant had spherical and pseudospherical forms with agglomeration traces and average size distribution of 59.66 ± 4.18 nm, which was under the standard error of the mean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results corroborated those of Ahluwalia et al [21], who reported that silver nanoparticles biosynthesized by T. harzianum exhibited spherical AgNPs with a range of diameters within the standard error of the mean. According to Tomah et al [36], SEM micrographs revealed that the exterior surfaces of AgNPs generated from cell-free T. virens HZA14 filtrate were spherical with a size range of 5 to 50 nm. Hirpara et al [24] demonstrated that silver nanoparticles biosynthesized by T. interfusant had spherical and pseudospherical forms with agglomeration traces and average size distribution of 59.66 ± 4.18 nm, which was under the standard error of the mean.…”
Section: Discussionmentioning
confidence: 99%
“…The results corroborated those of Konappa et al [20], who found the existence of AgNPs (58.75 percent) at 3 keV, followed by carbon, oxygen, and chlorine. According to Tomah et al [36], EDS examination of AgNPs found that pure silver (28.85 percent) at 3 KeV was the second most abundant component element after oxygen, nitrogen, carbon, and sulfur. Additionally, Manikandaselvi et al [37] revealed that significant signals were observed from the Ag atoms in the nanoparticles, in addition to signals from Al, carbon, and oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…A characterization of the synthesized AgCl-NPs was examined, as described by [ 10 ]. Surface characteristics and size of AgCl-NPs were observed using scanning electron microscopy (SEM) (Zeiss Gemini SEM 300, Jena, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, some of the biocontrol products in use were limited by geographical location due to the properties of biocontrol agents. These invited researchers to devise a new strategy to treat the plant diseases that plant pathogens caused, known as the biosynthesis of green nanoparticles [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts harbor various bioactive metabolites that could act as bio-reductants and stabilizers during the green synthesis of PtNPs [8][9][10][11]. In addition to plants, other biological entities were employed for green synthesis of PtNPs, including microbes (such as bacteria, viruses, fungi, and yeast) and marine algae [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The use of microbes as a potential biogenic route for the fabrication of PtNPs has some advantages, including their ease of production and capability to reduce Pt ions via enzymatic activity into the zero-valent Pt while maintaining optimum control over the average particle sizes [27].…”
Section: Introductionmentioning
confidence: 99%